(Im)Moral aspects of attitudes toward immigrants: the role of Dark Tetrad and Moral Foundations - Petrović, Boban (Psihološka istraživanja, 2019)
Immigration and refugee crisis is one of the major problems many European countries are currently facing, including transition countries, such as Serbia. Reactions toward refugees and immigrants from the Middle East and North Africa are polarized and raise the issue of moral aspects of attitudes towards them. Recently, human (im)morality was often investigated through concepts of Dark Tetrad traits and Moral Foundations. This research’s aim is to investigate the role of Dark Tetrad traits and Moral Foundations in the understanding of general and specific, situation-related pro-social attitudes toward immigrants. The results of this study (N=629 respondents from Serbia) showed that Harm/Care and Fairness/Reciprocity (Individual Foundations) correlated negatively, however Ingroup/Loyalty, Authority/Respect and Purity/Sanctity (Binding Foundations) correlated positively with Dark Tetrad traits. The general attitude toward immigrants was explained mainly by moral foundations: positive effect of Harm/Care and negative effects of Authority/Respect and Purity/Sanctity were detected, with the marginal negative effect of Machiavellianism. Specific attitude toward immigrants was explained both with the Dark Tetrad traits and the Moral Foundations. Expected positive effect of Fairness/Reciprocity and negative effects of sadism and Purity/Sanctity were also registered. Moral Foundations mediated the relationships between Dark Tetrad traits and both general and specific attitudes toward immigrants. Only narcissism and sadism have direct effects on attitudes toward them. Binding Foundations amplified, but Individual Foundations diminished negative effects of the Dark Tetrad traits to both general and specific attitudes toward immigrants. These results suggest that when people perceive threats from the ‘’others’’ to their inner circle, formal boundaries of morality are weakened and even most malicious personality traits are expressed.